2006
DOI: 10.1111/j.1349-7006.2006.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the treatment of peritoneal dissemination of gastrointestinal cancers by nucleoside antimetabolites

Abstract: Peritoneal dissemination is the most common cause of metastasis from malignancies in the abdominal cavity. There are no standard treatments for peritoneal dissemination and the results are poor. The reasons for this are as follows: (1) no effective chemotherapeutic agents have been identified or developed; (2) surgical cytoreduction has little effect on survival improvement; and (3) the molecular mechanisms of peritoneal dissemination have not been clarified and no therapy against the target molecules has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 72 publications
0
20
0
2
Order By: Relevance
“…The positive rate of tolemerase activity of the 37 specimens with serosal invasion was 54.1% (20/37), while PLC positive rate of those was 32.4% (12/37). As we know, serosal invasion appears to be mainly responsible for the exfoliation of free cancer cells into the peritoneal cavity [11] . It has been reported that approximately half of patients with serosal invasion develop peritoneal recurrence even if curative resection is performed [6,7,28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive rate of tolemerase activity of the 37 specimens with serosal invasion was 54.1% (20/37), while PLC positive rate of those was 32.4% (12/37). As we know, serosal invasion appears to be mainly responsible for the exfoliation of free cancer cells into the peritoneal cavity [11] . It has been reported that approximately half of patients with serosal invasion develop peritoneal recurrence even if curative resection is performed [6,7,28] .…”
Section: Discussionmentioning
confidence: 99%
“…Free cancer cells exfoliated from cancer lesions have been postulated as the main cause of metastasis [5,[8][9][10] . Recent advances on the molecular mechanisms of peritoneal dissemination have elucidated some of the target molecules and the development of new multimodal therapies in an attempt to eliminate peritoneal exfoliated www.wjgnet.com free cancer cells has also improved survival [11] . Of course, it is very important to develop reliable methods for the accurate selection of patients for whom adjuvant intraperitoneal therapy will be required.…”
Section: Introductionmentioning
confidence: 99%
“…There is no conclusive evidence, however, whether peritoneal dissemination might be established by the lymph node metastasis as well as direct dissemination from the serosal layer of stomach (Yonemura et al, 2007). In this study, the ID1 mRNA expression in bone marrow and peripheral blood was significantly associated with lymph node metastasis and peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 55%
“…Peritoneal dissemination is the most frequent type of recurrence in advanced gastric cancer (Jemal et al, 2005;Yoshikawa et al, 2006;Yonemura et al, 2007), and the prognosis for dissemination is the worst among the recurrence patterns of gastric cancer, with a mean survival of 6 months. Previous research indicated that peritoneal dissemination is required in many steps of the complex metastatic process, including the interaction of many genes along with their products, self-regulation, and interference with multiple signal transduction pathways (Yanagihara et al, 2005;Motoori et al, 2006).…”
Section: Introductionmentioning
confidence: 99%